PENINGKATAN DAYA TARIK WISATA DANAU KELIMUTU MELALUI TEKNOLOGI AUGMENTED REALITY - Prudensius Aprilianus M. Leru; Edwin A.U. Malahina (Jurnal Publikasi Manajemen Informatika, 2026)
This research aims to increase the tourist attraction of Lake Kelimutu through the application of Augmented Reality technology. Lake Kelimutu, which is famous for its three ever-changing colored lakes, has great potential as a tourist destination, but experiences challenges in presenting information to visitors. The application of AR is expected to provide interactive and educational experiences for tourists, enriching their understanding of the uniqueness of nature, history and local culture. This research will assess the effectiveness of AR in increasing tourist interest and satisfaction, as well as supporting environmental preservation. Through the exploration and development methods of AR applications, it is hoped that this research can contribute to the development of sustainable tourism on Lake Kelimutu, while inspiring innovation in the tourism sector in Indonesia.